New Cryptosporidium Genotypes in HIV-Infected Persons - Norman J. Pieniazek (Emerging Infectious Diseases, 1999)
Using DNA sequencing and phylogenetic analysis, we identified four distinct Cryptosporidium genotypes in HIV-infected patients: genotype 1 (human), genotype 2 (bovine) Cryptosporidium parvum, a genotype identical to C. felis, and one identical to a Cryptosporidium sp. isolate from a dog. This is the first identification of human infection with the latter two genotypes.